9x-8y=12

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 9x from both sides of the equation.

-8y=12-9x

Divide each term by -8 and simplify.

Divide each term in -8y=12-9x by -8.

-8y-8=12-8+-9x-8

Cancel the common factor of -8.

Cancel the common factor.

-8y-8=12-8+-9x-8

Divide y by 1.

y=12-8+-9x-8

y=12-8+-9x-8

Simplify 12-8+-9x-8.

Simplify each term.

Cancel the common factor of 12 and -8.

Factor 4 out of 12.

y=4(3)-8+-9x-8

Cancel the common factors.

Factor 4 out of -8.

y=4⋅34⋅-2+-9x-8

Cancel the common factor.

y=4⋅34⋅-2+-9x-8

Rewrite the expression.

y=3-2+-9x-8

y=3-2+-9x-8

y=3-2+-9x-8

Move the negative in front of the fraction.

y=-32+-9x-8

Dividing two negative values results in a positive value.

y=-32+9×8

y=-32+9×8

Reorder -32 and 9×8.

y=9×8-32

y=9×8-32

y=9×8-32

Rewrite in slope-intercept form.

y=98x-32

y=98x-32

Rewrite in Slope-Intercept Form 9x-8y=12